Do children's previous dental experience and fear affect their perceived oral health-related quality of life (OHRQoL)?. Issue 1 (December 2017) - Merdad, Leena; El-Housseiny, Azza
Abstract Background Oral health-related quality of life (OHRQoL) has been used to describe the consequences of oral health conditions and treatments in children. A better understanding of OHRQoL and its relationship with dental fear and previous dental experience is necessary to improve children's oral health status. The aim of this study was to investigate the association of dental history and experience with dental fear and the OHRQoL of children aged 11 to 14 years. Methods A cross-sectional study was conducted using a multi-stage stratified sample of 1, 312 middle school children. Information regarding OHRQoL was collected from the children using the Child Perceptions Questionnaire (CPQ11–14 ), and information regarding dental fear was collected using the Children's Fear Survey Schedule-Dental Subscale (CFSS-DS). Information on past dental experiences and sociodemographic data were collected from the parents using self-administered questionnaires. Dental examinations were performed to assess caries experience. Results The multivariable model indicated that dental fear was the strongest predictor of OHRQoL as the fearful children had on average CPQ11–14 scores that were 10 units higher than those of the non-fearful children. Regarding past dental experience, pain as the reason for the most recent dental visit was associated with poor OHRQoL, while receiving a filling during the previous dental visits was significantly associated with better OHRQoL. In addition, a larger number of siblings, a lower family income, a lower paternal education level, health problems and prior hospitalization were significantly associated with poor OHRQoL. Conclusion This study identified that dental fear and some factors related to previous dental experience are associated with OHRQoL. In dental practice, children with dental fear should be identified, guided and treated early to avoid deterioration of their OHRQoL.